TRADISI “MEDHOT BENANG LAWE” DALAM UPACARA PERKAWINAN NGLANGKAHI DI DESA PATIHAN KECAMATAN WIDANG KABUPATEN - Mahluk Attus Sholihak, Siti; Wayan Arsana, I (Jurnal Magister Hukum Perspektif, 2023)
This study examines the tradition of "Medhot Benang Lawe" in the Nglangkahi Marriage Ceremony in Patihan Village, Widang District, Tuban Regency. The purpose of this research is to: 1) Knowing the meaning contained in the tradition of Medhot Benang Lawe in the Nglangkahi marriage ceremony in Patihan Village, Widang District, Tuban Regency. 2) Understand the meaning contained in the means of Medhot Benang Lawe tradition in Nglangkahi marriage ceremony in Patihan village, Widang sub-district, Tuban regency. 3) Provide information about the values contained in the implementation of Medhot Benang Lawe in the Nglangkahi marriage ceremony in Patihan Village, Widang Subdistrict, Tuban Regency. This research uses juridical-empirical method by using sociological approach. The results of this study found that the Patihan Village Community still holds the Tradition of "Medhot Benang Lawe" in the Nglangkahi Marriage Ceremony when going ahead of an older sibling in a marriage. This tradition goes through a series of important processions. The tradition of "Medhot Benang Lawe" in the Nglangkahi Marriage Ceremony contains religious values, education and other important values in the lives of the people of Patihan Village, Widang District, Tuban Regency. Keywords: Tradition of "Medhot Benang Lawe", Nglangkahi Marriage.